Revolutionizing Freight Management: A Synergistic Approach Using IoT and Blockchain Technologies - Sujith Kumar Kupunarapu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative potential of integrating Internet of Things (IoT) and blockchain technologies in freight tracking and management. Traditional freight tracking methods often suffer from inaccuracies, delays, and lack of transparency, leading to inefficiencies across the supply chain. Integrating IoT devices, such as GPS trackers, RFID tags, and condition monitoring sensors, with blockchain’s secure and immutable ledger system offers a promising solution to these challenges. This article examines the current state of freight tracking, the fundamentals of IoT and blockchain technologies, and their combined application in creating real-time, secure, and transparent freight management systems. It discusses the benefits of this integrated approach, including enhanced visibility, improved efficiency, reduced disputes, and more agile supply chain operations. The article also addresses the challenges and considerations in implementing such systems, including technical hurdles, data privacy concerns, scalability issues, and regulatory requirements. Finally, it explores future prospects and research directions, such as the integration with AI and machine learning and the potential for expanding applications beyond tracking to areas like autonomous logistics. Through a comprehensive analysis of current implementations and future possibilities, this article provides valuable insights into how IoT-blockchain integration is poised to revolutionize the freight industry, offering a roadmap for more efficient, secure, and transparent global supply chains.